Pendekatan Teologis, Filosofis, dan Moderasi Beragama dalam Kurikulum Pendidikan Islam yang Relevan di Era Digital - Dede Asma Muslimah; M. Rizki Ramdhani A.; Resa Sepiadara; Muhamad Fuji Hakiki; Muhammad Ridwan Fauzi (Prodi Pendidikan Agama Islam, Institut KH. Ahmad Sanusi Sukabumi, 2025)
This study aims to describe the cultivation of religious values in the development of social intelligence among elementary school students at SDN Suryakencana CBM. A descriptive qualitative approach was employed in this research. Data were collected through observation, interviews, and documentation. The research participants consisted of the school principal, Islamic education teachers, homeroom teachers, and students. Data were analyzed using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion verification. The findings indicate that the cultivation of religious values has been systematically implemented through various school-based religious activities, such as congregational Duha prayer, Qur’an recitation (tadarus), congregational Dhuhr prayer, and Islamic commemorative events. These activities contribute to the formation of students’ religious dispositions, including discipline, obedience, and consistent engagement in worship practices. However, students’ social intelligence remains relatively underdeveloped, as evidenced by limited cooperation, insufficient empathy, and suboptimal peer interpersonal skills. These findings reveal a discrepancy between students’ high levels of ritual religiosity and their social intelligence development. In conclusion, while the implementation of religious values contributes positively to students’ religious character formation, it has not yet been fully effective in optimizing their social intelligence.